Perancangan dan Implementasi Website Sekolah sebagai Sarana Informasi Digital pada SDN Peninggilan 5 - Rosa Muthma'innah Sany; Isnaini Nursya Bania; Maulida Salsabila; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2026)
The development of information technology has brought significant changes in various sectors, including education. One of the applications of information technology in education is the use of websites as digital information media. SDN Peninggilan 5 requires an information system that can provide school information quickly, accurately, and easily accessible to the public. However, the current information dissemination process is still carried out manually, making it less effective and inaccessible in real time. This study aims to design and implement a school website as a digital information medium at SDN Peninggilan 5. The system was developed using the Waterfall method consisting of requirements analysis, system design, implementation, testing, and maintenance. The website was developed using PHP programming language and MySQL database. Data collection methods included observation, interviews, and literature studies. The results show that the developed website is capable of providing information regarding school profiles, vision and mission, teacher data, news, activity galleries, and contact information in a structured and accessible manner. Furthermore, the administrator system enables the school staff to independently manage and update information. Therefore, the school website can improve the effectiveness of information dissemination and support the digitalization of information services at SDN Peninggilan 5.